Acceptance of altmetrics by LIS scholars: An exploratory study. (September 2019) - Aharony, Noa; Bar-Ilan, Judit; Julien, Heidi; Benyamin-Kahana, Michal; Cooper, Tzipi
A survey of iSchool and Library and Information Science American Library Association accredited school heads explored their use and opinions about academic social media platforms. Results show that ResearchGate is the venue of choice, although respondents do not believe maintaining a profile on academic social media platforms influences academic careers. Respondents do see the value of academic social media sites to enhance visibility and reputation. These data are complemented with an analysis of the visibility on academic/professional social media platforms of this group. The altmetric indicators derived from the data were compared to traditional bibliometric indicators.